THE USE OF CONFERENCE VIDEO APPLICATION MEDIA “ZOOM” AS ALTERNATIVE MEDIA TO IMPROVE STUDENT’S SPEAKING ABILITY OF SOME STUDENTS AT SENIOR HIGH SCHOOL TWO JOMBANG - Fajar Shodik (Language-Edu, 2021)
ABSTRACT Shodik, Fajar.2020.THE USE OF CONFERENCE VIDEO APPLICATION MEDIA “ZOOM” AS ALTERNATIVE MEDIA TO IMPROVE STUDENT’S SPEAKING ABILITY OF SOME STUDENTS AT SENIOR HIGH SCHOOL TWO JOMBANG.Thesis, English Education Department, University of Islam Malang Postgraduate Program. Advisor: Dr.Muhammad Yunus, M.Pd. Key words: speaking ability, video conference, zoom application Abstract:this research aimed to take part to do the research with the different reason and the aim. The gaps in this current research is using online conference video media, to teach the students in senior high school, in the middle of virus pandemic period, especially in Indonesia. With the target of ability is speaking ability with supported by “zoom” conference video online as media which has function to improve the eleven grade form one of Senior High School two Jombang (SMAN 2 JOMBANG). And the result will be measured by knowing the increasing speaking ability score between students who use the online video media or not. Research problem here is to know How Can Zoom conference video application as alternative media are able to improve the student’s speaking ability for eleven grade at senior high school two jombang east java. the research objective here is This study tries to improve the effectiveness of Zoom conference video application as alternative media for student’s speaking ability at senior high school two jombang east java.            In this research applied Classroom action research to conduct it. By combining role play and think pare share learning method in applying during the research. And the next applying the two cycles, the researcher set up some actual ways to improve the speaking skill and the ability of eleven grade students at Senior high school two Jombang. with zoom conference video media. For the First, Actions using the "zoom" application are expected to be able or even more able to attract students' attention and also be able to motivate them in the teaching and learning process, especially in the pandemic era.Based on the application of the "zoom" application, it is hoped that it will be able to build a fun and attractive atmosphere, as well as add to a new teaching and learning experience on the demands of an online learning system.it can make the atmosphere in learning more fun and interesting. so that the students became more enthusiastic to show their mental condition. This method is believed to be more effective and suitable to make them have good self-confidence. The results of this study agreed with the increase in students' posttest scores. as a reference indicator shows which student's score for the Grammatical skills = 2.7, The Vocabulary = 2.6, Comprehension ability level = 2.6, fluency in speaking = 2.8, pronunciation skills = 2.6. it will answer or continued by showing posttest score after implemented Zoom as media in improving student’s speaking ability. The score is the Grammatical skills = 3.4, The Vocabulary = 3.3, Comprehension ability level = 3.5, fluency in speaking = 3.3, pronunciation skills = 3.5. from those data are able to said there is improvement for student’s speaking ability by using Zoom as alternative media and supporting media.